1999
DOI: 10.1086/302649
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of a Gene Determining Familial Partial Epilepsy with Variable Foci to Chromosome 22q11-q12

Abstract: We identified two large French-Canadian families segregating a familial partial epilepsy syndrome with variable foci (FPEVF) characterized by mostly nocturnal seizures arising from frontal, temporal, and occasionally occipital epileptic foci. There is no evidence for structural brain damage or permanent neurological dysfunction. The syndrome is inherited as an autosomal dominant trait with incomplete penetrance. We mapped the disease locus to a 3. 8-cM interval on chromosome 22q11-q12, between markers D22S1144… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 25 publications
5
65
1
Order By: Relevance
“…Observed cosegregation of a spectrum of clinical features in a Mendelian inheritance pattern can provide the basis for defining a syndrome, as was done for GEFS+ (64), autosomal dominant partial epilepsy with auditory features (52), and familial partial epilepsy with variable foci (77). Alternatively, families can be selected for analysis based on the correspondence of the symptoms of affected family members with the defined clinical epilepsy syndromes (20).…”
Section: Linkage Analysis Using Collections Of Small Familiesmentioning
confidence: 99%
“…Observed cosegregation of a spectrum of clinical features in a Mendelian inheritance pattern can provide the basis for defining a syndrome, as was done for GEFS+ (64), autosomal dominant partial epilepsy with auditory features (52), and familial partial epilepsy with variable foci (77). Alternatively, families can be selected for analysis based on the correspondence of the symptoms of affected family members with the defined clinical epilepsy syndromes (20).…”
Section: Linkage Analysis Using Collections Of Small Familiesmentioning
confidence: 99%
“…Familial partial epilepsy syndrome with variable foci (FPEVF), an autosomal dominant and clinically heterogeneous condition, was initially mapped in two large French -Canadian pedigrees to a B4 Mb interval on chr 22q11-12. 22 Two preceding studies confirmed linkage for FPEVF in Dutch, Spanish and French-Canadian pedigrees reporting a combined LOD score of 6.3 for the Spanish and three French -Canadian pedigrees. 23,24 Of note, members of these pedigrees are reported to have psychiatric problems including the diagnosis of paranoid schizophrenia.…”
Section: Discussionmentioning
confidence: 80%
“…Variable seizure severity between and within families is common. Structurally the brain appears normal Xiong et al 1999).…”
Section: Temporal Lobe Epilepsy (Tle)mentioning
confidence: 99%
“…However in FPEVF seizures are less frequent, tend to occur in clusters, frequently accompanied by auras. More frequent day-time and secondarily generalized seizures are seen in FPEVF than in ADNFLE (Berkovic et al 2004b;Xiong et al 1999). Variable seizure severity between and within families is common.…”
Section: Temporal Lobe Epilepsy (Tle)mentioning
confidence: 99%
See 1 more Smart Citation